Penerapan Prinsip Noodweer dalam Kasus Anak yang Berperkara Dengan Hukum Melalui Sistem Peradilan Pidana Anak - Agatha Nalaroses Thomas; Marthsian Y. Anakotta (Universitas Batanghari Jambi, 2022)
Children who have litigation with the law do not have a significant difference with adults who have litigation with the law. what makes a difference when a child has litigation with the law is in the justice system he is living in. The term child in the SPPA Law is associated with a child who has a conflict with a violation of the law, where the violation of the law is oriented towards the area of children and this is not indicated by the child perpetrator, but addressed to child victims and child witnesses who are legally protected. In a criminal act committed by a child, he is not necessarily spared or free from criminal prosecution. Against him is referred to as a child who is in litigation with the law. set. Whoever commits an act of forced defense for himself or for another person, honor, decency or property for himself or for another person, because there is an attack or threat of attack that is very close at that time which is against the law. So the forced defense carried out by children who are involved with the law will be considered according to the law of forced defense and the criminal law system of children.